Criteria for calculating damages for violation of fundamental rights. A systematic review of case law and a proposal for a scale - Todolí Signes, Adrián (LABOS Revista de Derecho del Trabajo y Protección Social, 2024)
The paper analyses the parameters used to justify compensation for non-pecuniary damages for infringement of fundamental rights in order to find out whether these parameters fit in with the legal objectives that such compensation must fulfil in accordance with art. 183 LRJS. At the same time, additional criteria are proposed which have not been found in judicial doctrine, but which are considered useful and necessary for compensation to fulfil its triple objective of being restorative, compensatory, and preventive. This work also proposes a formula for calculating compensation based on the parameters indicated by the Supreme Court and the LISOS itself, with the aim of making the calculation more objective and reducing legal uncertainty. This formula can also serve to increase the predictability of the compensation and to substantiate requests for a specific compensation for moral damages in the claim.
Keywords: Infringement of fundamental rights; non-pecuniary damage; 183 LRJS; punitive damages; additional compensation; parameters for calculating compensation; discrimination